GUIDELINES FOR PROMOTING UNDERSTANDING OF BLOCKCHAIN'S INFLUENCE ON BUSINESS OPERATIONS IN SERVICE SECTOR - Phimolsathien, T. (My University, 2022)
The objective of this study is to investigate the level of understanding of blockchain technology for businesses in the service sector and the level of impact of blockchain technology on business operations in the service sector, with the further aim of recommending readiness planning for the impact of blockchain technology on business operations in the service sector. The outcome of the study revealed that participants perceived the overall level of impact of blockchain technology on business operations in the service sector to be at mid-level. However, almost half of the participants were unsure about the level of impact of blockchain technology on business operations in the service sector. The issue about which most participants were uncertain was if the application of blockchain technology in businesses in the service sector could facilitate their work or coordination with suppliers. 58.40% of participants were unsure about this issue. Furthermore, the outcome of the study showed that understanding blockchain technology influenced the impact of blockchain technology on business operations in the service sector and could forecast 61.4% of the impact. As for readiness planning for the impact of blockchain technology on business operations in the service sector, it can be recommended that operators prepare their personnel and human resources, both in terms of numbers and capacity, to respond to changing trends in the market as well as basic understanding about blockchain technology. Operators should also prepare their business infrastructure by setting up a system to develop blockchain technology for management work within their organizations.
Keywords: Blockchain Technology; Impact of Blockchain Technology; Service Sector Business